Development of the Financial Services Market in the Conditions of Economic Turbulence - Ostrovska, N.; Popova, L.; Pylevych, D.; Panchenko, O.; Kozlianchenko, O.; Bazilinska, O. (International Journal of Computer Science and Network Security, 2022)
The article is devoted to the study of the development of the financial services market in conditions of economic turbulence. The concept, essence and approaches to its understanding are clarified. Stabilizing and destabilizing factors that affect the development of financial services market are identified. In order to study the development of financial services market in conditions of economic turbulence, the article focuses on its essence and leading manifestations. For the purpose of effective functioning in the conditions of economic turbulence the process of detection of turbulence and development of the corresponding actions taking into account preconditions, the reasons and catalysts of turbulent processes is offered. The main turbulent processes that negatively affect the development of the financial services market are identified, including: occupation of part of the territory, hostilities and further escalation of the conflict, political instability, devaluation of the national currency, deteriorating macroeconomic situation, reducing the number of financial services market participants. These processes are considered and their impac
Keywords: financial market, financial services market, development, turbulence, economic turbulence.